An Evidence-Based Logic for the Use of Positive Reinforcement: Responses to Typical Criticisms. (August 2020) - Scott, Terrance M.; Landrum, Timothy J.
In this article, we provide both a critical analysis of and logical response to a set of the most typical school-based objections to the effective use of positive reinforcement. For example, one objection is that positive reinforcement amounts to bribery. Practitioners are provided with clear and concise arguments refuting each objection and data-informed rationales supporting the school-based use of positive reinforcement.